Interprétations de la corrélation éducation-revenu - Lemelin, Clément (L'Actualité économique, 1984)
ABSTRACTBetter education means higher income. This correlation remains undisputed in the economics of education. Such is not the case for the meaning to be given to it. Why do better educated people earn more? Following Mark Blaug, various explanations are regrouped around three headings, economic, sociological and psychological interpretations, and they are briefly described. It is very difficult to choose among them since the questions they try to answer quite often differ. However, more recent work attempts to operate a synthesis by witholding some of the more fruitful elements of these various interpretations.